The addition of anaerobic fungi isolates from buffalo rumen to increase fiber digestibility, fermentation, and microbial population in ruminants - SINTA AGUSTINA; KOMANG GEDE WIRYAWAN; SRI SUHARTI; ANJA MERYANDINI (Society for Indonesian Biodiversity, 2024)
Abstract. Agustina S, Wiryawan KG, Suharti S, Meryandini A. 2024. The addition of anaerobic fungi isolates from buffalo rumen to increase fiber digestibility, fermentation, and microbial population in ruminants. Biodiversitas 25: 107-115. Rumen microbes have an important role in the rumen. Anaerobic fungi are microbes needed in the forage digestion process in the rumen. The addition of microbes, particularly anaerobic fungi is essential to increase the digestibility of forage within rumen. Therefore, this study aimed to evaluate the addition of anaerobic fungi isolates from buffalo rumen to increase fiber digestibility, fermentation, and microbial population in sheep rumen. The in vitro tests were carried out using the Tilley and Terry method, using elephant grass and rice straw as tested forage. Piromyces sp. (F1, and F3), Caecomyces sp. (F2, and F5), and Neocallimastix frontalis (F4) isolates from buffalo rumen were used as tested anaerobic fungi. The result showed that the addition of anaerobic fungi isolates from buffalo rumen significantly affected fiber digestibility (Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), cellulose and hemicellulose) except lignin digestibility. The addition of N. frontalis had higher fiber digestibility which is 49.02% NDF digestibility, 42.11% ADF digestibility, 44.28% hemicellulose digestibility, and 38.60% cellulose digestibility. Furthermore, N. frontalis also significantly increased In vitro Dry Matter Digestibility (IVDMD), In vitro Organic Matter Digestibility (IVOMD), ammonium (NH3) production, total Volatile Fatty Acid (VFA) production, and microbial population compared to Piromyces sp., and Caecomyces sp. In conclusion, anaerobic fungus type N. frontalis showed promising potential to be used as a ruminant probiotic due to its superior effect on fiber digestibility, fermentation, and microbial population compared to Caecomyces sp. and Piromyces sp.